2015
DOI: 10.1111/apt.13239
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence and its influence on disease course and surgery in Crohn's disease and ulcerative colitis

Abstract: Summary Background Smoking demonstrates divergent effects in Crohn's disease (CD) and ulcerative colitis (UC). Smoking frequency is greater in CD and deleterious to its disease course. Conversely, UC is primarily a disease of nonsmokers and ex‐smokers, with reports of disease amelioration in active smoking. Aim To determine the prevalence of smoking and its effects on disease progression and surgery in a well‐characterised cohort of inflammatory bowel diseases (IBD) patients. Methods Patients with smoking data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 62 publications
4
79
3
2
Order By: Relevance
“…Strengths of the study included the prospective design, use of time-dependent analysis and adjustment for confounding factors. The results generated, however, were similar to the Sydney IBD Cohort data,2 which comprised of analysis of prospectively collected data from a defined geographical population with a median of 9 years of follow-up (6275 patient-years) compared to 3 years (1557 patient-years) in this study. The limited power was demonstrated as wide CIs that could not demonstrate statistically significant reduction in need for surgery in quitters (IRR: 1.78, 95% CI 0.56 to 5.58)) or former smokers (IRR: 0.76: 95% CI 0.29 to 2.00), versus continuing smokers (IRR: 1.21, 95% CI 0.50 to 2.92).…”
Section: Commentarysupporting
confidence: 66%
“…Strengths of the study included the prospective design, use of time-dependent analysis and adjustment for confounding factors. The results generated, however, were similar to the Sydney IBD Cohort data,2 which comprised of analysis of prospectively collected data from a defined geographical population with a median of 9 years of follow-up (6275 patient-years) compared to 3 years (1557 patient-years) in this study. The limited power was demonstrated as wide CIs that could not demonstrate statistically significant reduction in need for surgery in quitters (IRR: 1.78, 95% CI 0.56 to 5.58)) or former smokers (IRR: 0.76: 95% CI 0.29 to 2.00), versus continuing smokers (IRR: 1.21, 95% CI 0.50 to 2.92).…”
Section: Commentarysupporting
confidence: 66%
“…First, it worsens CD, necessitating increased need for steroids and immunosuppressive drugs, more frequent relapses and surgery [126]. Moreover, current smokers have a two times higher risk and ex-smokers have a 1.8 times higher risk of developing CD in comparison to never-smokers.…”
Section: Impact Of Cs On Trp Channels In the Gut?mentioning
confidence: 99%
“…Previous studies have shown that smoking is both a risk factor for relapse of CD in general and for surgical recurrence in particular [14][15][16][17] . A recent multicenter prospective cohort study showed that despite the widespread use of immunosuppressants and anti-TNF antibodies, smokers with CD have a more severe disease course, including greater requirements for treatment, than non-smokers 18) .…”
Section: Discussionmentioning
confidence: 99%